A NEW GENUS OF THE GALERICINAE (ERINACEIDAE, INSECTIVORA, MAMMALIA) FROM THE MIDDLE EOCENE OF MONGOLIA - Lopatin A.V. (My University, 2004)
The earliest member of the subfamily Galericinae, Eogalericius butleri gen. et sp. nov., from the Middle Eocene Khaychin Formation of the Khaychin-Ula 2 locality is described. Eogalericius displays plesiomorphic similarity to Eochenus from the Middle Eocene of China. It is primitive in the following characters: P4-M2 are short, wide, and have small hypocones; the stylar lobes of M 1 and M2 and the parastyle of P4 are large and clearly project; P2 and P3 are nonreduced; P4 is relatively small with a well-developed metaconid and paraconid; in M1, the trigonid is short and the paracristid is subtransversely oriented; M3 has a hypoconulid; and two mental foramina are present.
Keywords: Galericinae; Erinaceidae; Middle Eocene; Mongolia; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен